Introduction. (July 2020) - Assmann, Ralph; Ferrario, Massimo
Abstract : 4th European Advanced Accelerators Concepts. More than 250 scientists from all over the world gathered from Sep 15 – 21 at the 4th European Advanced Accelerator Concept Workshop (EAAC) on the Island of Elba in Italy. Specialists from accelerator physics, RF technology, plasma physics, instrumentation and the laser field discussed ideas and directions towards a new generation of ultra compact and cost effective accelerators with ground-breaking applications in science, medicine and industry. The EAAC was founded by the European Network for Novel Accelerators (EuroNNAc) in 2013 and has grown in its fourth edition into a meeting with world-wide visibility, rapidly catching up with the long tradition of the Advanced Accelerator Concepts workshop (AAC) in the US. At the EAAC senior scientists from various specialties mix with junior experts and a large community of young students, attracted by the promise and success of compact particle accelerators. In 2019 about 50 PhD students presented their work at the EAAC. Besides the reports on scientific achievements the large diversity in gender, age distribution and nationalities made the EAAC 2019 a special event and a great success for the accelerator field. Group photo of the EAAC 2019 attendants is present in this pdf. Committees List of Workshop Organizing Committee, Programme Committee, International Advisory Committee, Local Organizing Committee and Proceedings Editors are available in this pdf.